Correlation Between Process Parameters and Mechanical Properties of Ti6Al4V Alloys Processed by Electron Beam Melting (Fracture and Structural Integrity, 2025)
The present study of Ti6Al4V alloy production via Electron Beam Melting (EBM) represents a cutting-edge research topic impacting different strategic engineering applications. This can be attributed to the widespread use of this alloy and by the unique characteristics of the EBM process. Operating under vacuum and with powder pre-heating, EBM enables the fabrication of components with higher density and reduced residual stress compared to other additive manufacturing techniques. The research reported in this paper analyses the effect of process parameters used in the manufacturing process on defect formation and then on mechanical properties. The results highlighted that the presence of lack of fusion defects leads to a markedly anisotropic behavior of the alloy. This is due to the different morphology of the defects in the different considered directions and to their effect in concentrating stresses.
Keywords: Additive Manufacturing; EBM process; Image analysis; Mechanical properties; Ti6Al4V alloy